Determination of sulfadiazine, trimethoprim, and N4‐acetyl‐sulfadiazine in fish muscle plus skin by Liquid Chromatography–Mass Spectrometry. Withdrawal‐time calculation after in‐feed administration in gilthead sea bream (Sparus aurata L.) fed two different diets. Issue 5 (14th March 2016) - Zonaras, V.; Tyrpenou, A.; Alexis, M.; Koupparis, M.
Abstract : This study presents a depletion study for sulfadiazine and trimethoprim in muscle plus skin of gilthead sea bream ( Sparus aurata L.). N 4 ‐acetyl‐sulfadiazine, the main metabolite of sulfadiazine (SDZ), was also examined. The fish were held in seawater at a temperature of 24–26 °C. SDZ and trimethoprim (TMP) were administered orally with medicated feed for five consecutive days at daily doses of 25 mg SDZ and 5 mg TMP per kg of fish body weight per day. Two different diets, fish oil‐ and plant oil‐based diets, were investigated. Ten fish were sampled at each of the days 1, 3, 5, 6, 8, 9, 10, and 12 after the start of veterinary medicine administration. However for the calculation of the withdrawal periods, sampling day 1 was set as 24 h after the last dose of the treatment. Fish samples were analyzed for SDZ, TMP, and acetyl‐sulfadiazine (AcSDZ) residues by liquid chromatography–mass spectrometry. SDZ and TMP concentrations declined rapidly from muscle plus skin. Considering a maximum residue limit of 100 μg/kg for the total of sulfonamides and 50 μg/kg for TMP residues in fish muscle plus skin, the withdrawal periods of the premix trimethoprim‐sulfadiazine 50% were calculated as 5 and 6 days, at 24–26 °C, in fish oil ( FO ) and plant oil ( PO ) groups, respectively. The investigation of this work is important to protect consumers by controlling the undesirable residues in fish.